Developing Flexibility in Mental Calculation - Elisabeth Rathgeb-Schnierer; Michael G. Green (Universidade Federal do Rio Grande do Sul, 2019)
Flexibility in performing mental calculations has become an important focus for mathematics educators, with research surging over the past two decades. Contemporary research results lends strong support for the development of mental flexibility in elementary classrooms. This report focuses on three interrelated themes: (1) a model of mental calculation that allows the study of flexible solution processes; (2) a review of definitions of flexibility and summary of reported research; and (3) an examination of the prerequisites for promoting mental flexibility. The approach termed Zahlenblickschulung is introduced with examples of activities that encourage students to sort numerical problems and reason about the sorting.